"The Community Policing Jakwire Wong Tegal" Program in Orders to Create a Conducive Community Security and Orders in the Legal Area of the County Police in Tegal City - Vebri Syintia Yunindra; Chairul Muriman Setyabudi; Surya Dharma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The efforts of the Tegal City Police to develop partnerships with various elements of society to jointly overcome the problems that exist in their environment through the "The Community Policing Jakwire Wong Tegal" Program. This research was conducted using a qualitative procedural approach to produce descriptive data. Collecting data by conducting personal interviews and questionnaires containing real information, facts and opinions collected from direct observations in the jurisdiction of the Tegal City Police. An overview of the research results shows that the "The Community Policing Jakwire Wong Tegal" program which is implemented in the jurisdiction of the Tegal City Police is a superior program that adopts the philosophy of the people of Tegal City which is thick with local culture as one of the characteristics of the coastal community (Pantura) which is simple, unpretentious and simple communicative, which does not show primodial barriers, but is formed in a social relationship both individuals and groups become "friends" which in Tegalan language means "jakwir". The program is designed to create a partnership between the National Police and community members who are able to identify, act and evaluate various problems, as well as improve the quality of life of the people of Tegal City. However, on the other hand, currently there are still some things that are less than optimal. For this reason, it is necessary to optimize the knowledge/ability of The Community Policing officers in understanding the culture of the people of Tegal City. Furthermore, it is suggested that the Polres Tegal City adopt/strengthen/sharpen/integrate the One Million Kawan the Community Policing program into the The Community Policing Jakwire Wong Tegal program through several models, including: 1) Local Development Model; 2) Social Planning Model; and 3) Social Action Model.